ANALISIS GANGGUAN PETIR AKIBAT SAMBARAN LANGSUNG PADA SALURAN TRANSMISI TEGANGAN EKSTRA TINGGI 500 kV - Abduh, Syamsir; Septian, Angga (Jurnal Teknik Elektro, 2009)
This paper summarizes the main results of a study aimed to figure the specific distortion and several factors that decreased the distortion. Lightning performance were combined between the distortion cause by shielding failure and back flashover, it using electro-geometrical and traveling wave theory. The result shows that increasing effectivity of ground wire shielding where the lightning is hitting phase wire which is definite by shielding angle, and preventing back flashover with minimum tower foot resistance and increasing coupling factor between ground wire and phase wire. Keywords: Lighning, ground wire, shielding